2007
DOI: 10.1177/089686080702700312
|View full text |Cite
|
Sign up to set email alerts
|

High Volume Peritoneal Dialysis for Acute Renal Failure

Abstract: Background Peritoneal dialysis (PD) is still widely used for acute renal failure (ARF) in developing countries despite concerns about its inadequacy. Continuous PD has been evaluated in ARF by analyzing the resolution of metabolic abnormality and normalization of plasma pH, bicarbonate, and potassium. Methodology A prospective study was performed on 30 ARF patients who were assigned to high-dose continuous PD (Kt/V = 0.65 per session) via a flexible catheter (Tenckhoff) and automated PD with a cycler. Fluid re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
107
3
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(123 citation statements)
references
References 28 publications
(49 reference statements)
11
107
3
2
Order By: Relevance
“…In addition, serum bicarbonate increased to above 20 mEq/L and serum potassium declined to less than 4 mEq/L (Table ) after 3–4 sessions of TPD. As in Ponce's study , we observed a shorter time to recovery of kidney function in patients treated with TPD compared to extracorporeal blood therapy [5 days (IQR 4‐6) days versus 8 days (IQR 7‐10)] for TPD and CVVHDF, respectively ( P < 0.01). In our study, the infectious complications were less common with TPD when compared with CVVHDF.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…In addition, serum bicarbonate increased to above 20 mEq/L and serum potassium declined to less than 4 mEq/L (Table ) after 3–4 sessions of TPD. As in Ponce's study , we observed a shorter time to recovery of kidney function in patients treated with TPD compared to extracorporeal blood therapy [5 days (IQR 4‐6) days versus 8 days (IQR 7‐10)] for TPD and CVVHDF, respectively ( P < 0.01). In our study, the infectious complications were less common with TPD when compared with CVVHDF.…”
Section: Discussionsupporting
confidence: 77%
“…Compared with the previous randomized trial of Ponce et al that did not show differences in terms of survival or recovery of renal functions between HD and high‐volume PD, our results demonstrated a remarkable difference in favor of TPD over CVVHDF (survival rates of 69.8% vs. 46.8%, P < 0.01). While Katirtzoglou et al reported BUN levels below 100 mg/dL which were considered satisfactory at that time for patients with AKI treated with continuous PD, Gabriel and colleagues achieved BUN values around 50 mg/dL and creatinine at <4 mg/dL with high volume peritoneal dialysis used for treatment of AKI in the ICU setting. Chitalia et al demonstrated that CPD was able to maintain BUN levels at about 65 mg/dL in mild and moderate hypercatabolic AKI patients from India.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An often-overlooked modality of CRRT in the ICU is peritoneal dialysis (PD). A study conducted in Brazil reported effective treatment of critically ill patients with AKI using high-volume PD [24]. In countries where contemporary modalities of CRRT are not available, highvolume PD may be a good alternative.…”
Section: Discussionmentioning
confidence: 99%
“…They reported that both methods, CPD and tidal PD, provided an adequate dialysis dose. A Brazilian group has recently published an interesting paper, 6 bringing PD back to the frontline and giving many doctors, in countries with limited resources, the opportunity to treat their patients with a simple and efficacious technique. Gabriel et al 6 concluded in their study that high-dose continuous PD using Tenckhoff PD catheter and APD with a cycler was an effective treatment for ARF, allowing appropriate metabolic and acid-base control as well as adequate dialysis dose and fluid removal.…”
Section: Abstract: Emergency Dialysis; Severe Hyperkalemia; Automatedmentioning
confidence: 99%